Jokowi Effect or Krisdayanti Effect? An Analysis of the Phenomenon of Reverse Coattail Effect by Celebrity Politics in the 2019 Concurrent Election - Dewa, Talitha Zerlina Surya; Sobari, Wawan; Pohan, Ibnu Asqori (Universitas Brawijaya, 2020)
Previous studies on the relationship between the electability of presidential and legislative candidates in Indonesia followed the coattail effect theory. The decision to vote for presidential candidate contributes to the decision to vote for a party or legislative candidate. Nonetheless, this theory is not entirely appropriate in explaining the electability of celebrity legislator candidate in the 2019 Concurrent Election. The case study of elected celebrity politics Krisdayanti in the constituency of East Java V (Malang Regency, Malang City, Batu City) in the 2019 Concurrent Election shows an opposite logic. The decision to vote for Krisdayanti actually led to the decision to vote for the Candidate Pair Joko Widodo-Ma'ruf Amin (Jokowi-Ma'ruf) or it shows the working of the reverse coattail effect theory. Krisdayanti operationally performed dual role as a celebrity politician and celebrity endorser for Jokowi-Ma'ruf. Krisdayanti's electoral influence endorse constituents to vote for Jokowi-Ma'ruf. If it is not used as the main consideration, the voters admit that Krisdayanti's endorsement is able to strengthen their decision to vote for Jokowi-Ma'ruf. In other words, the operation of the reverse coattail effect theory shows the Krisdayanti effect encourage and strengthen the decision to vote for Jokowi-Mar'ruf.